2007
DOI: 10.1161/01.hyp.0000258151.00728.d8
|View full text |Cite
|
Sign up to set email alerts
|

Less Atherosclerosis and Lower Blood Pressure for a Meaningful Life Perspective With More Brain

Abstract: T raditional teaching subdivides the dementia syndrome into neurodegenerative Alzheimer's disease (AD), vascular dementia (VaD), and mixed variants. In spite of the vast and continuing literature on the dichotomy between AD and VaD, new emerging concepts highlight the role of cardiovascular risk factors in the pathogenesis of AD, especially in older patients. 1,2 Hypertension is the major player in the pathogenesis of stroke, poststroke dementia, and VaD. AD is the most common cause of dementia, contributing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 93 publications
1
70
0
6
Order By: Relevance
“…The identification of this group of patients is more complicated than identifying subjects with vascular risk factorsthis could be done by recruiting patients with cognitive complaints and a confirmed deficit on validated neuropsychological tests. As vascular pathologies may have greater impact on non-memory cognitive domains such as executive dysfunction and processing speed, 56 inclusion criteria should not be restricted to only those with memory impairment but be broadened to individuals with deficits in any defined cognitive domain. The possibility of selecting subjects at high vascular risk within this group (patients with clinical risk factors or lesions due to small-vessel disease on neuroimaging) also becomes an important consideration.…”
Section: Toward the Design Of A Dementia Pre-vention Studymentioning
confidence: 99%
“…The identification of this group of patients is more complicated than identifying subjects with vascular risk factorsthis could be done by recruiting patients with cognitive complaints and a confirmed deficit on validated neuropsychological tests. As vascular pathologies may have greater impact on non-memory cognitive domains such as executive dysfunction and processing speed, 56 inclusion criteria should not be restricted to only those with memory impairment but be broadened to individuals with deficits in any defined cognitive domain. The possibility of selecting subjects at high vascular risk within this group (patients with clinical risk factors or lesions due to small-vessel disease on neuroimaging) also becomes an important consideration.…”
Section: Toward the Design Of A Dementia Pre-vention Studymentioning
confidence: 99%
“…1 Because populations are aging, the number of demented patients will grow 2-fold every 20 years, from 24.3 million people in 2000 to 81.1 million by 2040, with Ͼ60% living in developing countries. 2 The question of whether hypertension is a modifiable risk factor for dementia is therefore of great clinical importance.…”
Section: Placebo-controlled Trials Of Blood Pressure-lowering Therapimentioning
confidence: 99%
“…The pooled odds ratios were 0.75 (CI, 0.60 to 0.94; Pϭ0.01) for Systolic Hypertension in the Elderly Program (SHEP), 3 SystEur, 5 and the combination therapy arm of PROGRESS, 4 and 1.08 (CI, 0.84 to 1.38; Pϭ0.54) for SCOPE 6 and the perindopril-only subgroup of the PROGRESS trial. 4 Since our 2007 review, 1 4 additional placebo-controlled trials reported on the prevention of dementia by blood pressurelowering therapies, including ADVANCE, 7 HYVET-COG, 8 PRoFESS, 9 and, most recently, TRANSCEND. 10 We therefore updated our meta-analysis ( Figure).…”
Section: Placebo-controlled Trials Of Blood Pressure-lowering Therapimentioning
confidence: 99%
“…Hay escaso número de ensayos aleatorizados sobre el tratamiento antihipertensivo que han utilizado las lesiones cerebrales y la disfunción cognitiva como variables de valoración 404 . Un pequeño subestudio del ensayo PROGRESS ha explorado el efecto de la reducción de la presión arterial en la progresión de la afección de la sustancia blanca (imágenes de resonancia magnéti-ca), y ha observado una reducción significativa del volumen total medio de nuevas lesiones en el grupo en el que perindopril junto con indapamida redujo la presión arterial en 11/4 mmHg más que placebo 405 .…”
Section: Cerebro Y Función Cognitivaunclassified